Physicochemical characteristics of reduced graphene oxide based Pt‐nanoparticles‐conducting polymer nanocomposite film for immunosensor applications. Issue 9 (6th August 2014) - Puri, Nidhi; Mishra, Sujeet K.; Niazi, Asad; Srivastava, Avanish K.; Rajesh
Abstract BACKGROUND This study describes, electrochemically prepared Pt‐nanoparticles (PtNP) embedded poly(pyrrole‐co‐pyrrolepropylic acid) (PPy‐PPa) copolymer film over reduced graphene oxide (RGO) sheets deposited on a silane modified indium‐tin‐oxide coated glass plate. The cardiac myoglobin protein antibody (Ab‐Mb) was covalently immobilized on PtNP(PPy‐PPa)‐RGO nanocomposite through pendant carboxyl groups of the polymer chain using carbodiimide coupling reaction to construct a bioelectrode. The bioelectrode was characterized by high resolution transmission electron microscopy, energy dispersive spectra and electrochemical impedance spectroscopy (EIS). The sensing performance of the bioelectrode was investigated, as an impedimetric immunosensor, for the quantitative detection of the target human cardiac myoglobin antigen (Ag‐cMb) in phosphate buffer silane (pH 7.4). RESULTS The EIS studies of the bioelectrode towards Ag‐cMb showed a dominant charge transfer resistance (Ret) characteristic in the frequency region 50 to 100 Hz. The EIS of the bioelectrode showed an effective immunoreaction with Ag‐cMb with a significant increase in both Ret and the constant phase element parameter (n) from 0.61 to 0.85. The bioelectrode exhibited a linear dynamic range of detection from 10 ng mL−1 to 1 µg mL−1, sensitivity of 107.08 Ω cm2 per decade and a lowest detection limit of 4.0 ng mL−1 Ag‐cMb. CONCLUSION The polymer nanocomposite with uniformly distributed PtNP in conjunction with conducting RGO support has been demonstrated to be a high performance immunosensor. This has been attributed to the synergistic combination of conducting RGO support and electroactive PtNP embedded conducting functional copolymer for efficient covalent biomolecular immobilization, responsible for high protein loading and fast interfacial electron exchange. © 2014 Society of Chemical Industry